Frequency and costs of pulmonary exacerbations in patients with cystic fibrosis in the United States. (3rd April 2017) - Rubin, Jaime L.; Thayer, Sarah; Watkins, Angela; Wagener, Jeffrey S.; Hodgkins, Paul S.; Schechter, Michael S.
Abstract: Background: Information is limited regarding the cost of pulmonary exacerbations (PEx) among patients with cystic fibrosis in the United States. Methods: To examine PEx costs, medical chart data were linked to insurance claims for patients aged ≥6 years who had commercial coverage from a large US health insurer affiliated with Optum during 2008–2013. A PEx was categorized as an episode requiring newly started (1) oral antibiotics (PEx-O) or (2) intravenous (IV) antibiotics and/or inpatient stay (PEx-IV). Results: Among 241 patients, 88.0% had ≥1 PEx (2.9/year) of any type, and 48.1% had ≥1 PEx-IV. Prior PEx-IV was the strongest risk factor for subsequent PEx-IV. The mean cost per episode was 12, 784 for PEx of any type and 36, 319 for PEx-IV. Patients with worse lung function were more likely to experience a PEx and incurred higher annual PEx-related costs. Limitations: This was an observational study using a convenience sample of patients with commercial coverage from a large US health insurer whose medical charts were available for abstraction. Results of the study may not be generalizable to individuals with Medicaid coverage and other types of insurance, or to the uninsured. Conclusions: Most patients experience ≥1 PEx annually, and nearly half require IV antibiotics and/or inpatient stay at considerable cost.